IBD-associated Colon Cancers Differ in DNA Methylation and Gene Expression Profiles Compared With Sporadic Colon Cancers. (11th February 2019) - Pekow, Joel; Hernandez, Kyle; Meckel, Katherine; Deng, Zifeng; Haider, Haider I; Khalil, Abdurahman; Zhang, Chunling; Talisila, Nitya; Siva, Shivi; Jasmine, Farzana; Li, Yan Chun; Rubin, David T; et al.
Abstract: Background and Aims: As ulcerative colitis [UC]-associated colorectal cancer [CRC] and sporadic CRC differ in presentation and molecular features, we sought to evaluate differences in the impact of DNA methylation on gene expression. Methods: DNA methylation was assessed in 11 UC-CRCs and adjacent tissue and 11 sporadic CRCs and adjacent tissue, using Illumina arrays. RNA sequencing was performed on 10 UC-CRCs and adjacent tissue and eight sporadic CRCs and adjacent tissues. Differences in DNA methylation and transcript expression, as well as their correlation in the same tissues, were assessed. Immunohistochemistry was performed for three proteins, ANPEP, FAM92A1, and STK31, all of which exhibited an inverse correlation between DNA methylation and transcript expression in UC. Results: Thirty three loci demonstrated differences in DNA methylation between UC-CRC and adjacent tissue. In contrast, there were 4204 differentially methylated loci between sporadic colon cancer and adjacent tissue. Eight hundred eighty six genes as well as 10 long non-coding RNAs [lncRNA] were differentially expressed between UC-CRC and adjacent tissues. Although there were no differentially methylated loci between UC and sporadic CRC, 997 genes and 38 lncRNAs were differentially expressed between UC-CRC and sporadic CRC. In UC, 18 genes demonstrated a negative correlation between DNA methylation and transcript expression. Evaluation of protein expression related to three genes, ANPEP, FAM92A1, and STK31, confirmed down-regulation of ANPEP and up-regulation of STK31 in UC-CRC. Conclusions: Regulation of transcript expression by DNA methylation involves genes key to colon carcinogenesis and may account for differences in presentation and outcomes between inflammatory bowel disease and sporadic colon cancer.